(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2025)
This study aims to describe the implementation of listening skills as the foundation of English language learning at SDII Luqman Al Hakim 02 Batam. The research focuses on teachers’ strategies in integrating listening activities, the media used, and students’ responses toward the learning process. This research employed a qualitative descriptive approach. Data were collected through classroom observations, interviews with teachers and students, and documentation of learning materials. The data analysis was conducted using Miles and Huberman’s model, which includes data reduction, data display, and conclusion drawing. The findings reveal that listening skills serve as the basis for developing students’ language competence, particularly in speaking and vocabulary building. Teachers applied various strategies, such as songs, interactive games, and audio-visual media, to enhance students’ comprehension. Students showed positive responses, indicated by their increased participation and enthusiasm in classroom activities. This research highlights that listening is a crucial foundation in English language learning at the elementary school level and needs to be developed through the support of diverse media and teaching methods.